2016
DOI: 10.1051/0004-6361/201527357
|View full text |Cite
|
Sign up to set email alerts
|

Hot bubbles of planetary nebulae with hydrogen-deficient winds

Abstract: Heat conduction has been found a plausible solution to explain discrepancies between expected and measured temperatures in hot bubbles of planetary nebulae (PNe). While the heat conduction process depends on the chemical composition, to date it has been exclusively studied for pure hydrogen plasmas in PNe. A smaller population of PNe show hydrogen-deficient and helium-and carbonenriched surfaces surrounded by bubbles of the same composition; considerable differences are expected in physical properties of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For instance, at early times we could expect the abundances to be dominated by hot, shocked stellar wind material, while at later times nebular abundances will determine the spectral characteristics. This is more relevant for the case of PNe with [WR]-type nuclei and has been recently explored by Sandin et al (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, at early times we could expect the abundances to be dominated by hot, shocked stellar wind material, while at later times nebular abundances will determine the spectral characteristics. This is more relevant for the case of PNe with [WR]-type nuclei and has been recently explored by Sandin et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, they favoured the numerical results from their efficient conduction method, arguing that the low-efficiency conduction method results in limb-brightened synthetic X-ray surface brightness profiles, which did not match some observations at the time. This group has recently extended its numerical simulations to study the X-ray emission from PNe with hydrogen-deficient winds (Sandin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-hydrodynamic simulations of these hot bubbles and their x-ray emission have been carried out by several groups. Steffen, Schönberner, & Warmuth (2008) and Sandin et al (2016) demonstrated the importance of thermal conduction at the interface between the shocked wind and the nebular gas. Toalá & Arthur (2014 performed high-resolution two-dimensional calculations following the evolution of these hot bubbles.…”
Section: Nebular Shaping: the Interacting Winds Modelmentioning
confidence: 99%
“…Supporting evidence for heat conduction has been found from multi-wavelength studies of the 10 5 K transition region (see Ruiz et al 2013 and the contribution by Guerrero in this volume). Studies of heat conduction in nebula with distinct chemical compositions are ongoing (see Sandin et al 2016 and the contribution by Schoenberner in this volume). Other predictions of heat conduction models, such as the radial distribution of hot bubble emission (Freeman & Kastner 2016) and mixing of nebular and fast wind elemental abundances (Maness & Vrtilek 2003) are limited by the capabilities of the two modern X-ray observatories.…”
Section: Insights From X-ray Emission From Planetary Nebulaementioning
confidence: 99%